Anomalous vibrational excitation in the small angle scattering of He+ from HCl at Elab=20-60 eV - Thomas , Ruhaltinger; Jan Peter , Toennies; Ruigang , Wang; Ibrahim Ali , Noorbatcha; Susanta , Mahapatra; Narayanasami , Sathyamurthy (American Chemical Society, USA, 1995)
Energy loss spectra of forward scattered He+ ions in collisions with HCl are reported for collision energies (E(lab)) in the range 20-60 eV. The spectra extend up to total energy transfers of about 2.5 eV, where the intensity is 6 orders of magnitude less than the elastic forward peak. At large energy transfers a number of broad maxima indicating a propensity for large Delta v transitions are observed. Three-dimensional quasiclassical trajectory calculations treating HCl as a rigid rotor for the long range ion-dipole/quadrupole He+-HCl interaction and a short range repulsion corresponding to the isoelectronic He+-Ar account for much of the energy transfer at low Delta E. At higher Delta E, the rigid rotor model is dearly inadequate and a better description of the experiment requires consideration of high lying repulsive states of HCl+ which appear to be temporarily accessed by charge transfer.